Influence of External Factors on Airborne Missile’s Horizontal Backward Launching - Xiao Pan; Yi Jiang; Dong Hu; Huihui Guan (International Journal of Aerospace Engineering)
This paper studies the influence of different external disturbance factors on the horizontal backward separation of airborne missiles on large transport aircraft. The method of comparison with experiment was adopted to verify the accuracy of the finite element model during the ejection process. By comparing the finite element model, it was confirmed that the all rigid body model and partly rigid body model are inaccurate in calculating the pitch angle and pitch velocity of the missile separation. Finally, the influences of ejection force, random vibration, and missile loading position on the ejection process are analyzed. The analysis found that the ejection force and the sliding distance will increase the vibration of the launching platform, therefore increase the separation pitch angle and the pitch velocity of the missile, but the influence of random vibration on platform is much greater than the other two factors, and it will also introduce randomness into the movement of the missile.